Educación Matemática en el período de pandemia de Covid-19, República Dominicana - González, Sarah (2021)
In this paper, we present several aspects of Mathematics Education characterization in the Covid-19 pandemic period in the Dominican Republic. Also, macro state decisions on the educational area that framework the Mathematics Education development in this period are included. As in most of the countries in the Latin American region, the teaching and learn- ing processes were organized as virtual learning through TV, radio, computers, tablets, cell phones, internet, and printed booklets. The Ministry of education made extraordinary efforts to develop three daily hours of video classes for each grade, these classes are repeated in two shifts, mornings and afternoons. Eighteen TV channels and tens of radio stations were contracted to broadcast the classes. Also, the videos are published daily in a YouTube channel. 60,000 laptops for teachers and around 1,800,000 tablets and laptops for students were distributed, connectivity limitations showed up so the TV and radio acquired higher importance. Teachers, students, and families communicate mainly through What’s app. The official curriculum was modified focusing in the development of the Fundamental Compe- tencies of the curriculum. An example of the comparison of a theme from the fourth grade Mathematics Curriculum is included. Also, it is included a summary of how the Mathemat- ics Education was approached in the Instituto Superior de Formación de Docentes (Higher Education Institute for Teacher Education) during pandemic.